The critique of action research in Administration as a way of recovering its potential for transformative action - Angélica Pereira Soares; Débora Coutinho Paschoal Dourado (Contextus, 2022)
This article aimed to analyze how the action research has been applied in the field of Administration in Brazil. A bibliographical research was carried out from the Scientific Periodicals Electronic Library (SPELL). For the research corpus, 22 articles were selected, analyzed from four predefined categories: intervention, intervention with participation, beneficiaries, and sociopolitical or technical aspects. The findings indicate that most of the analyzed articles use action research in a limited way, reducing it to a technique for solving management issues and deviating its transformative potentiality. Here, we highlight the importance of an action research that considers the context of those involved, so that ready-made solutions are not applied to the problems of the studied collectivity.